Wind Power Balancing using Flywheel Energy Storage System - Ažubalis, Mindaugas; Baranauskas, Audrius; Tamulis, Giedrius (Elektronika ir Elektrotechnika, 2013)
The paper presents analysis of feasibility of wind parks’ connection to the transmission network considering the grid capacity. The methodic for determination of maximum permissible power of wind parks is presented. Wind parks’ connection in Lithuanian power system is analysed. Normal, maintenance and emergency conditions of Baltic power system operating autonomously, synchronously and asynchronously with IPS/UPS and the power system of Continental Europe are considered. Possibilities of the western part of Lithuanian power system’s transmission network of 110 and 330 kV to transmit power generated by wind parks are evaluated. Partitioning of the transmission grid into zones with evaluated maximum permissible power of wind parks and their groups as well as connection locations are presented. DOI: http://dx.doi.org/10.5755/j01.eee.19.1.1431